On Strong Summability of Fourier Series of Summable Functions - Pachulia, N. L. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
In the metric of L, we obtain estimates for the generalized means of deviations of partial Fourier sums from an arbitrary summable function in terms of the corresponding means of its best approximations by trigonometric polynomials.